Methicillin Resistant Staphylococcus Epidermidis Induced Endogenous Endophthalmitis - Undrakonda Vivekanand; Pradeep Pakalapati; Gudimetla Sandeep Reddy; Sritej Talluri (Journal of Clinical and Diagnostic Research, 2014)
Fulminant endogenous endophthalmits, a relatively rare intraocular infection, caused by haematogenous spread of bacteria or fungi is usually seen in immune-deficient patients. We report a case of methicillin resistant Staphylococcus epidermidis causing endogenous endophthalmitis following platelet transfusion and intravenous antibiotic therapy for a suspected dengue fever.